Pitfalls, Complications, and Necessity of Education about REBOA: A Single Regional Trauma Center Study - Sol Kim; Jae Sik Chung; Sung Woo Jang; Pil Young Jung (Journal of Trauma and Injury)
Purpose Resuscitative endovascular balloon occlusion of the aorta (REBOA) is an emergency procedure and extremely time-dependent, and the proficiency of the physician is important. Due to a lack of REBOA education programs in Republic of Korea, few physicians have been trained in the procedure. In this study, we examined how REBOA education affects clinical outcomes in a single center. Methods A retrospective study conducted from February 2017 to June 2020 at a regional trauma center. We collected data of patients who underwent REBOA and analyzed the factors that influenced the outcome. The patients were divided into the educated and non-educated groups (based on REBOA training received by their physicians), and the success and failure groups. Results A total of 24 patients underwent REBOA during the study. There were eight patients in the success group and 16 patients in the failure group. There are no significant differences between the educated and non-educated groups in sex, age, ISS, shock, injury-to-REBOA time, injury mechanism, injury sites, arrest, access site, type of catheter, type of REBOA, target Zone, mortality, and the result of REBOA. The non-educated group had a higher risk for failure compared to the educated group in multivariate analysis (odds ratio [OR] 154.64, 95% confidence interval [CI] 1.11-22.60). Conclusions Failure in REBOA is harmful to patients. The risk of failure is increased in the non-educated group. Physicians working in the trauma center or emergency department need to complete the REBOA education program.